Social networks as one of the instruments of accumulation and illegal use of personal data of citizens - Роман Федорович Черниш (Проблеми Законності, 2017)
It is well known that in recent years, social networks have ceased to be exclusively a tool for communication. Every day, millions of users around the world provide information (including personal data), which at any moment can be used either against them or, in certain circumstances, to the detriment of national interests. Especially sharply delineated issues raised for our country in terms of its actual stay in a state of undeclared war. However, attention should be paid to the fact that a significant part of the personal data of users of social networks reported voluntarily. Most social networks involves placing personal page on name, date of birth, gender, place of birth (residence) place of study / work, office, information about family position, information on parents, brothers / sisters, children and so on. In most, the user account contains different statistical characteristics of his stay in the system, date, time and duration of the last entry and stay in the system, the address used when connecting a computer and more. We can conclude that each page of a user’s social network – is readily available and relatively unlimited archive of his personal data. The issue of preserving a secret personal given users is important and requires its further scientific development. Given the need to ensure adequate protection of constitutional rights and national interests from illegal encroachments, within the framework of the planned measures provided for by the Decree of the President of Ukraine №32 / 2017 «On the decision of the National Security and Defense of Ukraine of 29 December 2016» On the state and threats cyber security urgent measures to neutralize them», it seems necessary at the highest state authorities to take immediate steps for the development of innovative approaches to protecting the interests of individuals, society and the state in the information sphere.